Multimorbidade em pessoas idosas hospitalizadas - Schmidt, Leucinéia (2022)
Population aging has intensified in recent years, associated with the epidemiological transition characterized by the increase in chronic diseases. Multimorbidity, the presence of two or more chronic diseases, can cause greater functional decline, frailty, reduced life expectancy, increased hospitalization time in the older adults and impact on quality of life, among other factors. Thus, the objective of this study was to verify the association between the presence of multimorbidity and sociodemographic, nutritional variables and health conditions in older adults hospitalized in a hospital in the interior of Rio Grande do Sul. Cross-sectional study, with hospitalized older adults of both genders, with 60 years or older. The sociodemographic variables were: sex, age, skin color, education, marital status, who they live with, whether they have paid work and health services. Nutritional status was assessed using the mini nutritional assessment and health conditions were: functionality, frailty, self-perception of health and length of hospital stay. The tests were applied: chi-square, Fishers exact, t test and Poisson multiple regression. A total of 261 older adults participated, with a mean age of 73,03±8,44 years. It was found that 83.9% had multimorbidity, being associated in the bivariate analysis with gender, age, paid activity, nutritional status, functionality and frailty. However, in the multivariate analysis, it was associated with a lower prevalence of multimorbidity, only older adults who had paid work, who were hospitalized through the Unified Health System (SUS) and with a lower score on the frailty scale. The results indicated that multimorbidity was lower in older adults with paid work, who were hospitalized through the SUS and with a lower rate of frailty. These three factors were relevant among the older adults in this study and require more attention from the scientific community and health managers to improve public policies aimed at older adults with multimorbidity. All results will be presented in the form of a scientific production that will later be submitted to a journal in the area.